Subclinical Ketosis in Dairy Herds: Impact of Early Diagnosis and Treatment - Cascone, Giuseppe; Licitra, Francesca; Stamilla, Alessandro; Amore, Simona; Dipasquale, Mario; Salonia, Rosario; Antoci, Francesco; Zecconi, Alfonso (Frontiers in Veterinary Science, 2022)
Clinical and subclinical ketosis (SCK) in dairy cows occurs during the lactation period frequently in many herds, causing the reduction in milk yield and alterations in milk quality with significant economic losses for farmers. SCK is defined as a preclinical stage of ketosis characterized by an elevate ketone body level without clinical signs. Often many cows develop an elevated ketone body level during the first weeks of lactation even though it never goes up to critical point causing clinical signs. This study aimed to evaluate the of SCK and provide the results of a treatment with propylene glycol (PG) to control the SCK. The survey was carried out on 22 farms located South-east of Sicily and 1588 cows in lactation. A total of 3989 samples were collected from calving to 80 subsequently days to determine the contents of: fat, protein, lactose, casein, urea, somatic cell count, β- hydroxybutyrate (BHB) and Acetone, in order to establish the SCK status of cows by ketonic level evaluation. The results showed a BHB values frequency higher than 0.10 mmol/L considering the entire population, mostly during the first 10 days of lactation. Subsequently, the animals in SCK stage were treated with PG (400mg) and the treatment resulted much more effective in the first days of lactation than the following days. PG positively influenced the parameter and improved significantly all the components evaluated, excepted the quantity of fat. Therefore, the animals treated with PG showed also an increase in milk yield, confirming the positive effect of treatment, economically sustainable.